Pengaruh Pembelajaran Aktif Berbantuan Media Bonus (Boneka Nusantara) Terhadap Hasil Belajar IPS - Yuka Rahmah Tiara Cahya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the active learning model assisted bythe BONUS (Boneka Nusantara) media on social studies learning outcomes for fourthgrade students at SD N Sukorejo Magelang.This research is a type of experimental research with Pre-experimentalresearch design with the